MINIMAL CLINICALLY IMPORTANT DIFFERENCE OF THE LATE-LIFE FUNCTION AND DISABILITY INSTRUMENT IN OLDER ADULTS. (11th November 2018) - Beauchamp, M; Ward, R; Jette, A; Bean, J
Abstract: The Late-Life Function and Disability Instrument (LLFDI) is a well validated and frequently used patient-reported outcome measure in older adults. The aim of this study was to provide the first estimates of the minimal clinically important difference (MCID) of the LLFDI-Function Component (LLFDI-FC) and its subscales among community-dwelling older adults with mobility limitations. We performed a secondary analysis of the Boston Rehabilitative Impairment Study of the Elderly, a longitudinal cohort study of older adults with mobility limitations residing in the community. The MCID for each LLFDI-FC scale over 1-year of follow-up was estimated using both anchor and distribution-based methods including mean change scores on a patient-reported global rating of change in function scale (GRC), the standard error of measurement (SEM), and the minimal detectable change with 90% confidence (MDC90). Data from 320 older adults were used in the analysis (mean age 76, 69% female, mean of 4 chronic conditions). Meaningful change estimates for "small change" based on the GRC and SEM were 2, 3, 4 and 4 points for the LLFDI-FC overall function scale and basic lower-extremity, advanced lower-extremity and upper-extremity sub-scales, respectively. Estimates for "substantial change" based on the GRC and MDC90 were 5, 6, 9 and 10 for the overall function scale and basic lower-extremity, advanced lower-extremity and upper-extremity sub-scales, respectively. These MCID estimates can be used to interpret the outcomes of longitudinal investigations of functional status in similar populations of community-dwelling older adults.